Variations and driving mechanism of dissolved arsenic in sediment porewater near wetland. (February 2022) - Yu, Chen; Guo, Huaming; Zhang, Chaoran; Chen, Dou; Ye, Haolin
Abstract: The special hydrogeological conditions of wetland easily lead to the formation of high-arsenic (As) groundwater. However, it is unclear relative contribution of wetland water (surface water) dissolved organic matter (DOM) and sedimentary organic matter (SOM) to porewater DOM and its relations with dissolved As under the wetland. Porewater, groundwater and sediment samples were taken to monitor spatial-temporal variations in dissolved As affected by fluctuation of surface water levels near a typical wetland with high As groundwater in the arid-semiarid Hetao Basin, China. Hydrochemical data showed that As concentrations of sediment porewater (average: 17.1 μg/L) lay between As concentrations of surface water (average: 6.48 μg/L) and groundwater (average: 184 μg/L). A long-term observation showed concentrations of dissolved As, Fe, and dissolved organic carbon (DOC) of porewater obviously increased when levels of surface water rose during waterlogging period. There were positive correlations between dissolved As and Fe (r = 0.69, p < 0.01) and dissolved As and DOC (r = 0.38, p < 0.01). The sequential extraction showed that the main As form in sediment was amorphous Fe(III) oxide-coprecipitated form (averagely 45.0% of total As). It indicates that the dissolved As in porewater mainly originated from the Fe(III) oxide-bound forms in the sediment. Fluorescence indices and parallel factor analysis of the three-dimensional fluorescence spectra showed that porewater DOM mainly derived mainly from SOM during the drought period and from both surface water DOM and SOM during the waterlogging period. Higher proportions of As(III) in porewaters during waterlogging period were observed relative to those during drought period, indicating that surface water infiltration led to relatively reducing conditions. Surface water infiltration introduced DOM and stimulated the release of SOM into the porewater. DOM, acting as electron donor and electron shuttle, triggered the reductive dissolution of Fe(III) oxides, leading to the As mobilization under the wetland. This study suggests that drinking water supply near wetlands should be concerned, since high concentrations of dissolved As normally occurred in shallow aquifers near the wetland. Highlights: Porewater As, Fe, and DOC increased when wetland water level rose. Arsenic-bearing Fe(III) oxides in sediments were the main source of porewater As. Infiltration of surface water input DOM and mobilized sediment OM into porewater. DOM triggered reductive dissolution of Fe(III) oxides, leading to As mobilization.